# Vigre 2009: algebraic geometry

 Page 3 / 3

Lemma 3.1 [link] Formula 1.1.2 Given a continued fraction $\left[{r}_{1},{r}_{2},{r}_{3},...\right],{h}_{v}$ and k v satisfy the following recursions:

${h}_{v}={r}_{v}{h}_{v-1}+{h}_{v-2},\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}{h}_{-1}=1,{h}_{-2}=0$
${k}_{v}={r}_{v}{k}_{v-1}+{k}_{v-2},\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}{k}_{-1}=0,{k}_{-2}=1.$

Lemma 3.2 [link] Formula 1.2.1 Given a continued fraction as above, A v satisfies the following relations:

$\begin{array}{cc}\hfill {A}_{\delta }& \ge {A}_{v}\phantom{\rule{1.em}{0ex}}v\phantom{\rule{0.166667em}{0ex}}odd\hfill \\ \hfill {A}_{\delta }& \le {A}_{v}\phantom{\rule{1.em}{0ex}}v\phantom{\rule{0.166667em}{0ex}}even.\hfill \end{array}$

Moreover, this means that ${A}_{v}\le {A}_{v+1}$ for odd v.

The following is a claim about the n 's from the Euclidean Algorithm.

Lemma 3.3 In the above notation, ${n}_{v}={\left(-1\right)}^{v}\left(p{h}_{v}-{k}_{v}q\right)$ .

This will be done by induction with two base cases. If $v=1$ , then

${n}_{1}=q-p{r}_{1}=-\left(p{r}_{1}-q\right)=-\left(p{h}_{1}-{k}_{1}q\right).$

If $v=2$ , then

${n}_{2}=p-{r}_{2}{n}_{1}=p-{r}_{2}\left(q-{r}_{1}p\right)=p\left({r}_{1}{r}_{2}+1\right)-{r}_{2}q={\left(-1\right)}^{2}\left(p{h}_{2}-{k}_{2}q\right).$

Now we will assume the claim is true for v and $v+1$ and we will prove that it is true for $v+2$ . From the Euclidean algorithm, we have that

${n}_{v+2}={n}_{v}-{r}_{v+2}{n}_{v+1}$
$={\left(-1\right)}^{v}\left(p{h}_{v}-{k}_{v}q\right)-{\left(-1\right)}^{v+1}{r}_{v+2}\left(p{h}_{v+1}-{k}_{v+1}q\right).$

For v even, using Lemma [link] we obtain

${n}_{v+2}=p\left({h}_{v}+{r}_{v+2}{h}_{v+1}\right)-\left({k}_{v}+{r}_{v+2}{k}_{v+1}\right)q=p{h}_{v+2}-{k}_{v+2}q.$

If v is odd, using Lemma [link] we have

${n}_{v+2}=-p\left({h}_{v}+{r}_{v+2}{h}_{v+1}\right)+\left({k}_{v}+{r}_{v+2}{k}_{v+1}\right)q=-\left(p{h}_{v+2}-{k}_{v+2}q\right).$

Since v and $v+2$ will be either both even or both odd, this proves the claim. The following lemmas relate recursions that occur in the proof of Theorem [link] to continued fraction expressions.

Lemma 3.4 Suppose $\left\{{C}_{i}\right\}$ is a sequence of integers satisfying the following recurrence relation

${C}_{i}=\left({C}_{i-1}+{n}_{i-1}\right){r}_{i}+{C}_{i-2},\phantom{\rule{1.em}{0ex}}{C}_{1}={r}_{1}p,\phantom{\rule{0.166667em}{0ex}}{C}_{2}={r}_{2}q.$

Then

${C}_{v}=\left\{\begin{array}{cc}p{h}_{v}\hfill & v\phantom{\rule{0.166667em}{0ex}}odd\hfill \\ q{k}_{v}\hfill & v\phantom{\rule{0.166667em}{0ex}}even.\hfill \end{array}\right)$

This is done by induction again. For $v=1$ and $v=2$ , the initial conditions of the recursion of C give ${C}_{1}=p{h}_{1}$ and ${C}_{2}=q{k}_{2}$ . Now we assume that the claim is true for v and $v+1$ and we will prove that it is true for $v+2$ . First, we have

${C}_{v+2}=\left({C}_{v+1}+{n}_{v+1}\right){r}_{v+2}-{C}_{v}=\left[{C}_{v+1}+{\left(-1\right)}^{v+1}\left(p{h}_{v+1}-{k}_{v+1}q\right)\right]{r}_{v+2}-{C}_{v}$

by the original recursion of C i and Lemma [link] . There are two cases. First we will consider the case where v is odd. Then

${C}_{v+2}=\left(q{k}_{v+1}+p{h}_{v+1}-{k}_{v+1}q\right){r}_{v+2}+p{h}_{v}$

by the inductive hypothesis. It follows from Lemma [link] that

${C}_{v+2}=p\left({h}_{v+1}{r}_{v+2}+{h}_{v}\right)=p{h}_{v+2}.$

Now consider the case where v is even. Then

${C}_{v+2}=\left(p{h}_{v+1}-p{h}_{v+1}+{k}_{v+1}q\right){r}_{v+2}+q{k}_{v}$

by the inductive hypothesis. It follows from Lemma [link] that

${C}_{v+2}=q\left({k}_{v+1}{r}_{v+2}+{k}_{v}\right)=q{k}_{v+2}.$

This proves the claim.

Lemma 3.5 Suppose that $\left\{{K}_{i}\right\}$ is a sequence of integers satisfying the following recurrence relation

${K}_{i}=\left({K}_{i-1}+1\right){r}_{i}+{K}_{i-2},\phantom{\rule{1.em}{0ex}}{K}_{1}={r}_{1},{K}_{2}={r}_{2}\left({r}_{1}+1\right).$

Then ${K}_{v}+1={h}_{v}+{k}_{v}$ .

We again use induction with two base cases. First, if $v=1$ , then

${K}_{1}+1={r}_{1}+1={h}_{1}+{k}_{1}.$

Second, if $v=2$ , then

${K}_{2}+1={r}_{2}\left({r}_{1}+1\right)+1={r}_{2}{r}_{1}+{r}_{2}+1={h}_{2}+{k}_{2}.$

Now we will assume that the claim is true for v and $v+1$ and we will prove that it is true for $v+2$ . By the original recursion of K i ,

${K}_{v+2}+1=\left({K}_{v+1}+1\right){r}_{v+2}+{K}_{v}+1.$

Then by the inductive hypothesis,

$\begin{array}{cc}\hfill {K}_{v+2}+1& =\left({h}_{v+1}+{k}_{v+1}\right){r}_{v+2}+{h}_{v}+{k}_{v}\hfill \\ & =\left({h}_{v+1}{r}_{v+2}+{h}_{v}\right)+\left({k}_{v+1}{r}_{v+2}+{k}_{v}\right)\hfill \\ & ={h}_{v+2}+{k}_{v+2}\hfill \end{array}$

by the recursion of k v and h v from Lemma [link] . This proves the claim.

## Proof of theorem

Without loss of generality, assume that $q\ge p$ . For this proof, we will use a “reduced” notion of blow-ups in which consecutive blow-ups that use the same variable will be reduced to a single blow-up. For example, if we have three typical blow-up steps with $y=sx$ , $s=tx$ , and $t=ax$ , we will combine these to be $y=a{x}^{3}$ . Note that the multiplicities of these blow-ups are the same. We will soon justify the use of these blow up “chains”.

We will use the equations from the Euclidean algorithm as in the previous section. The number of r i 's used will be the number of blow-ups needed, and the value of r i will be the degree of the variable at that particular blow-up (e.g. ${r}_{i}=3$ in the previous example). Note that the r i values can also be expressed as the continued fraction of $\frac{q}{p}$ as $\left[{r}_{1},{r}_{2},...,{r}_{\delta }\right]$ . Let C i be the multiplicity of the ${i}^{th}$ exceptional divisor and let K i be the log canonical multiplicity of the differential form of the ${i}^{th}$ blow-up. We claim that the multiplicities K i and C i satisfy the following recursions:

${K}_{i}=\left({K}_{i-1}+1\right){r}_{i}+{K}_{i-2},\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}{K}_{1}={r}_{1},{K}_{2}={r}_{2}\left({r}_{1}+1\right),$
${C}_{i}=\left({C}_{i-1}+{n}_{i-1}\right){r}_{i}+{C}_{i-2},\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}\phantom{\rule{0.166667em}{0ex}}{C}_{1}={r}_{1}p,{C}_{2}={r}_{2}q.$

First, it is easy to check that ${K}_{1}={r}_{1}$ and ${K}_{2}={r}_{2}\left({r}_{1}+1\right)$ . Then, after $i-1$ blow-ups, our differential form ihas the form

${{t}_{i-2}}^{{K}_{i-2}}{{t}_{i-1}}^{{K}_{i-1}}d{t}_{i-1}d{t}_{i-2}.$

By definition of r i , the next iterated blow up includes the substitution ${t}_{i-1}={t}_{i}{{t}_{i-2}}^{{r}_{i}}$ . We obtain the differential form

${{t}_{i-2}}^{{K}_{i-2}}{\left({t}_{i}{{t}_{i-2}}^{{r}_{i}}\right)}^{{K}_{i-1}}{{t}_{i-2}}^{{r}_{i}}d{t}_{i-2}d{t}_{i}={{t}_{i}}^{{K}_{i-1}}{{t}_{i-2}}^{\left({K}_{i-1}+1\right){r}_{i}+{K}_{i-2}}d{t}_{i-2}d{t}_{i}.$

Thus, ${K}_{i}=\left({K}_{i-1}+1\right){r}_{i}+{K}_{i-2}$ .

It is also easy to check that ${C}_{1}=p{r}_{1}$ and ${C}_{2}=q{r}_{2}$ . After $i-1$ blow-ups the equation is

${{t}_{i-2}}^{{C}_{i-2}}{{t}_{i-1}}^{{C}_{i-1}}\left({{t}_{i-2}}^{{n}_{i-2}}-{{t}_{i-1}}^{{n}_{i-1}}\right).$

By definition of r i , the next iterated blow up includes the substitution of ${t}_{i-1}={t}_{i}{{t}_{i-2}}^{{r}_{i}}$ . We obtain the new equation

${{t}_{i}}^{{C}_{i-1}}{{t}_{i-2}}^{{C}_{i-2}+{r}_{i}{C}_{i-1}}\left({{t}_{i-2}}^{{n}_{i-2}}-{{t}_{i}}^{{n}_{i-1}}{{t}_{i-2}}^{{r}_{i}{n}_{i-1}}\right)$
$={{t}_{i}}^{{C}_{i-1}}{{t}_{i-2}}^{\left({C}_{i-1}+{n}_{i-1}\right){r}_{i}+{C}_{i-2}}\left({{t}_{i-2}}^{{n}_{i}}-{{t}_{i}}^{{n}_{i-1}}\right).$

Thus, ${C}_{i}=\left({C}_{i-1}+{n}_{i-1}\right){r}_{i}+{C}_{i-2}$ .

The recursion relations for C i and K i allow us to apply Lemma [link] to C i and Lemma [link] to K i . Now we can justify the notion of blow-ups that groups together consecutive substitutions of the same variable into “chains.” It is not entirely clear that substitutions within a given chain do not yield smaller contributions to the LCT. To show that the smallest contribution to the LCT from a particular chain comes from its final substitution, we need to show that each successive substitution within such a chain decreases the contribution of the chain to the LCT. Let j be the number of blow-ups within the ${i}^{th}$ chain. To prove the above statement, it would suffice to show that

$\frac{\left({K}_{i-1}+1\right)j+{K}_{i-2}+1}{\left({C}_{i-1}+{n}_{i-1}\right)j+{C}_{i-2}}\ge \frac{\left({K}_{i-1}+1\right)\left(j+1\right)+{K}_{i-2}+1}{\left({C}_{i-1}+{n}_{i-1}\right)\left(j+1\right)+{C}_{i-2}},$

which is true if and only if

$\left({C}_{i-1}+{n}_{i-1}\right)\left({K}_{i-2}+1\right)\ge {C}_{i-2}\left({K}_{i-1}+1\right).$

We will show that this is true using two cases. First, assume that i is even. Then the above equation becomes

$\left(q{k}_{i-1}\right)\left({h}_{i-2}+{k}_{i-2}\right)\ge \left(q{k}_{i-2}\right)\left({h}_{i-1}+{k}_{i-1}\right)$

$⇕$

${A}_{i-2}+1\ge {A}_{i-1}+1,$

which is true for even i by Lemma [link] . Now we will assume i is odd. Then the previous expression becomes

$\left(p{h}_{i-1}\right)\left({h}_{i-2}+{k}_{i-2}\right)\ge \left(p{h}_{i-2}\right)\left({h}_{i-1}+{k}_{i-1}\right)$

$⇕$

$\frac{1}{{A}_{i-2}}+1\ge \frac{1}{{A}_{i-1}}+1$

$⇕$

${A}_{i-2}\le {A}_{i-1},$

which is true for odd i by Lemma [link] . This shows that the LCT will be determined by these chains.

We will now show that the final chain determines the LCT. Thus, we want to show that ${\alpha }_{\delta }\le {\alpha }_{v}$ for all v . First, we will introduce the notation for ${A}_{v}=\frac{{h}_{v}}{{k}_{v}}$ to be the expression of the ${v}^{th}$ convergent. We must consider two cases. First, if v is odd, then

${\alpha }_{\delta }\le {\alpha }_{v}$

$⇕$

$\frac{{h}_{\delta }+{k}_{\delta }}{p{h}_{\delta }}\le \frac{{h}_{v}+{k}_{v}}{p{h}_{v}}$

$⇕$

$1+\frac{1}{{A}_{\delta }}\le 1+\frac{1}{{A}_{v}}$

$⇕$

$\frac{1}{{A}_{\delta }}\le \frac{1}{{A}_{v}}$

$⇕$

${A}_{\delta }\ge {A}_{v}.$

This last statement is true by Lemma [link] , so for v odd, ${\alpha }_{\delta }\le {\alpha }_{v}$ . If v is even, then

${\alpha }_{\delta }\le {\alpha }_{v}$

$⇕$

$\frac{{h}_{\delta }+{k}_{\delta }}{q{k}_{\delta }}\le \frac{{h}_{v}+{k}_{v}}{q{k}_{v}}$

$⇕$

$1+{A}_{\delta }\le 1+{A}_{v}$

$⇕$

${A}_{\delta }\le {A}_{v}$

$⇕$

${A}_{\delta }\le {A}_{v}.$

This last statement is also true by Lemma [link] , so for v even, ${\alpha }_{\delta }\le {\alpha }_{v}$ . Thus, ${\alpha }_{\delta }\le {\alpha }_{v}$ for all $v<\delta$ .

It only remains to show that ${\alpha }_{\delta }=\frac{1}{p}+\frac{1}{q}$ . We know that $\frac{q}{p}=\frac{{h}_{\delta }}{{k}_{\delta }}$ , which is to say $q{k}_{\delta }=p{h}_{\delta }$ , so by Lemma [link] ${C}_{\delta }=q{k}_{\delta }$ for both odd and even δ . Thus,

${\alpha }_{\delta }=\frac{{K}_{\delta }+1}{{C}_{\delta }}=\frac{{h}_{\delta }+{k}_{\delta }}{q{k}_{\delta }}=\frac{\frac{{h}_{\delta }}{{k}_{\delta }}+1}{q}=\frac{\frac{q}{p}+1}{q}=\frac{1}{p}+\frac{1}{q}.$

This concludes the proof of the theorem.

what is the stm
is there industrial application of fullrenes. What is the method to prepare fullrene on large scale.?
Rafiq
industrial application...? mmm I think on the medical side as drug carrier, but you should go deeper on your research, I may be wrong
Damian
How we are making nano material?
what is a peer
What is meant by 'nano scale'?
What is STMs full form?
LITNING
scanning tunneling microscope
Sahil
how nano science is used for hydrophobicity
Santosh
Do u think that Graphene and Fullrene fiber can be used to make Air Plane body structure the lightest and strongest. Rafiq
Rafiq
what is differents between GO and RGO?
Mahi
what is simplest way to understand the applications of nano robots used to detect the cancer affected cell of human body.? How this robot is carried to required site of body cell.? what will be the carrier material and how can be detected that correct delivery of drug is done Rafiq
Rafiq
what is Nano technology ?
write examples of Nano molecule?
Bob
The nanotechnology is as new science, to scale nanometric
brayan
nanotechnology is the study, desing, synthesis, manipulation and application of materials and functional systems through control of matter at nanoscale
Damian
Is there any normative that regulates the use of silver nanoparticles?
what king of growth are you checking .?
Renato
What fields keep nano created devices from performing or assimulating ? Magnetic fields ? Are do they assimilate ?
why we need to study biomolecules, molecular biology in nanotechnology?
?
Kyle
yes I'm doing my masters in nanotechnology, we are being studying all these domains as well..
why?
what school?
Kyle
biomolecules are e building blocks of every organics and inorganic materials.
Joe
anyone know any internet site where one can find nanotechnology papers?
research.net
kanaga
sciencedirect big data base
Ernesto
Introduction about quantum dots in nanotechnology
what does nano mean?
nano basically means 10^(-9). nanometer is a unit to measure length.
Bharti
do you think it's worthwhile in the long term to study the effects and possibilities of nanotechnology on viral treatment?
absolutely yes
Daniel
how to know photocatalytic properties of tio2 nanoparticles...what to do now
it is a goid question and i want to know the answer as well
Maciej
Abigail
for teaching engĺish at school how nano technology help us
Anassong
How can I make nanorobot?
Lily
Do somebody tell me a best nano engineering book for beginners?
there is no specific books for beginners but there is book called principle of nanotechnology
NANO
how can I make nanorobot?
Lily
what is fullerene does it is used to make bukky balls
are you nano engineer ?
s.
fullerene is a bucky ball aka Carbon 60 molecule. It was name by the architect Fuller. He design the geodesic dome. it resembles a soccer ball.
Tarell
what is the actual application of fullerenes nowadays?
Damian
That is a great question Damian. best way to answer that question is to Google it. there are hundreds of applications for buck minister fullerenes, from medical to aerospace. you can also find plenty of research papers that will give you great detail on the potential applications of fullerenes.
Tarell
Got questions? Join the online conversation and get instant answers!